Raptor Hacking - Pratt, Mike (Wildlife Rehabilitation Bulletin, 2011)
In the raptor rehabilitation field, hacking is a special procedure for raising juvenile raptors that simulates natural fledging and allows young raptors—those that cannot yet fly and either are still restricted to or just leaving the nest—a gradual acclimation to independence. Hacking also is known as a ‘soft release.’ This paper focuses on hacking raptors and discusses advantages, disadvantages, hacking age, procedures, hack box design and construction, site selection, fledging age of raptor species, and hack release.